Dialogic Imagination in the Book of Deuteronomy - Robert Polzin (Studies in 20th & 21st Century Literature, 1984)
One of the profoundest insights into the syntax of narrative is the complex system of relationships between reporting and reported speech worked out in programmatic form by Voloshinov-Bakhtin in a number of groundbreaking studies (for example, in English translation, Marxism and the Philosophy of Language by V.N. Voloshinov and The Dialogic Imagination by Bakhtin). Interesting literary insights into texts that have been studied and interpreted over centuries and even milennia now await the application by present-day scholars of Bakhtin's theories. The Book of Deuteronomy offers a unique opportunity within the Bible of applying the reported/reporting speech approach of Bakhtin. The entire book of thirty-four chapters consists of a series of reported speeches of Moses framed with only about fifty-six verses by the reporting speech of the Deuteronomic narrator. The dynamic relationship of these two voices in the book provides one with a reading of Deuteronomy that significantly departs from the predominant scholarly view.
Keywords: syntax of narrative; reporting; reported; speech; Voloshinov-Bakhtin; Deuteronomy; Marxism and the Philosophy of Language; V.N. Voloshinov; Dialogic Imagination; Bakhtin; Book of Deuteronomy; Bible; Moses; narrator